Denmark : Financial Sector Assessment Program; Detailed Assessment of the Securities Clearance and Settlement Systems. (IMF Staff Country Reports; Country Report, 2007)
This paper discusses key findings of the Detailed Assessment of the Securities Clearance and Settlement Systems for Denmark. The assessment recommends that securities settlement systems should have a well-founded, clear, and transparent legal basis in the relevant jurisdiction. Confirmation of trades between market participants should occur as soon as possible after trade execution, but no later than trade date (T+0). Where confirmation of trades by indirect market participants is required, it should occur as soon as possible after trade execution, preferably on T+0, but no later than T+1.